THE INFLUENCE OF SERVICE QUALITY AND PRICES IS MEDIATED BY CONSUMER SATISFACTION ON REPEAT PURCHASE AT HALAL RESTAURANTS IN THE CITY OF BANDA ACEH - Nikmatullah, Muhammad; Kesuma, Teuku Meldi (Universitas Syiah Kuala, 2024)
This research aims to analyze the influence of service quality and price on repeat purchases at halal restaurants in Banda Aceh with consumer satisfaction as a mediating variable. Samples used. The objects of this research are the people of Banda Aceh who have visited halal restaurants. This research uses a quantitative approach, with a non-probability sampling method using purposive sampling technique with a sample size of 100 respondents. The data used in this research are primary data and secondary data. Primary data was obtained from distributing questionnaires to respondents and secondary data from literature study. The analysis used is descriptive analysis. Based on the results of the research analysis, it was found that service quality had a positive and significant effect on repeat purchases. Consumer Satisfaction partially mediates the influence of Service Quality and Price on Repeat Purchases.